Intercultural Communication Apprehension (ICA) among BA and MA Students - Rimkeeratikul, Sucharat (LEARN Journal: Language Education and Acquisition Research Network, 2024)
The research was conducted at a public university in Bangkok, utilizing the Personal Report on Intercultural Communication Apprehension (PRICA) to measure Intercultural Communication Apprehension (ICA). The study aimed to compare the ICA levels among three groups of students within the same university: bachelor’s degree students majoring in Business Administration, MA students majoring in English, and MA students majoring in Political Science. All classes were held on the same campus. An Analysis of Variance (ANOVA) was employed to analyze the differences in anxiety levels among these groups. The findings indicated that undergraduate students exhibited higher levels of ICA compared to the MA students from different majors. These results provide valuable insights for EFL teachers and the administration, enabling them to develop strategies to reduce student anxiety. This, in turn, could help ensure that intercultural communication does not become a barrier to societal development in the era of globalization.